How to develop four competencies for teacher educators - Nguyen, Ngan Thi Lan (Frontiers in Education, 2023)
Understanding competencies and the process of acquiring them contributes to a shared set of essential abilities for teacher educators’ professional development. Practical experiences of practitioners expose which competencies the work context requires them to possess and situations in which their learning is conducted. The necessity for essential contextual competency is pressing, particularly for teacher educators working in developing countries where teacher education has undergone reforms to respond to national and international demands. This study explores competencies for teacher educators in Vietnam through in-depth interviews with experienced practitioners and their visual metaphors. Eight participants with working experience ranging from 6 to 26 years were interviewed for 60–180 min during January–April 2021. The results reveal four competency areas of (1) knowledge and skills consisting of (a) teaching skill, (b) subject content, (c) scientific and subject-related information, (d) the reality of education and multidisciplinary knowledge, (e) research procedural knowledge, (f) collaboration with others, and (g) English language; (2) ethical manner; (3) motivation; and (4) self-reflection about personal values. Professional development includes learning from and working with others, learning in organized courses, conducting independent and collaborative research, and other field-related academic activities. An interesting highlight is that even motivational competency is gradually formed by professionals’ effort put into work. The findings suggest these four competency components should be attended to when providing professional development activities for teacher educators. Motivational competency should be prioritized since it fosters job productivity and commitment. The findings also serve as practical guidance for self-preparation and development for those working as teacher educators in demanding contexts.